SPECIFIC FEATURES OF ERYTHROPOIETIN EXPRESSION IN THIRD-TRIMESTER PLACENTAS IN CASE OF ACUTE COVID-19 - Ищенко, Людмила Станиславовна; Воропаева, Екатерина Евгеньевна; Казачкова, Элла Алексеевна; Казачков, Евгений Леонидович; Холопова, Анна Юрьевна (Medicine in Kuzbass, 2025)
The aim of the research is to evaluate the expression of erythropoietin in the placentas of women with acute COVID-19 in the third trimester of gestation. Materials and methods. Retrospective study. The main group included 7 placentas from patients with extremely severe COVID-19 and a serum EPO level of 4.7 (4.4; 9.3) mIU/ml. The comparison group consisted of 19 placentas from patients with mild, moderate, or severe COVID-19 and a serum EPO level of 17 (6.9; 22.0) mIU/ml. The expression of the immunohistochemical marker of hypoxia, erythropoietin, in the placenta was studied. Results. Erythropoietin expression was detected in the syncytiotrophoblast, capillary endothelium, and villous stromal cells of patients with any severity of acute COVID-19. Despite a statistically significantly lower serum erythropoietin level in pregnant women with extremely severe COVID-19, erythropoietin expression in the placentas from this group was statistically significantly more pronounced compared to placentas in case of other degrees of infection severity. Conclusion. COVID-19 is accompanied by significant placental disorders of a hypoxic nature, regardless of the severity of the infection. A higher level of erythropoietin expression in the placenta of pregnant women with extremely severe COVID-19, accompanied by low serum erythropoietin levels, indicates the activation of autocrine mechanisms for local erythropoietin synthesis to compensate for severe hypoxia in the organ.